Surgical outcome of Acoustic Neuroma Surgery in a Malaysian Tertiary Hospital - Razak, Siti Sarah; Abdullah, Asma; Hashim, Noor Dina; Abu Bakar, Azizi; Sutan, Rosnah; Sani, Abdullah (IIUM Medical Journal Malaysia, 2024)
INTRODUCTION: Acoustic neuroma (AN) or vestibular schwannoma, is a benign, slow-growing tumour that arises from the Schwann cell of the vestibular branch of the vestibulocochlear nerve. Treatment options are mainly conservative or surgical excision. The aim of this study is to describe the clinical characteristics of AN and the surgical outcomes in a Malaysian tertiary hospital. MATERIALS AND METHOD: Records of 73 patients who were diagnosed with AN from January 2008 until December 2019 were retrieved. All patients were analyzed for demographic data and clinical characteristics. In all 52 patients underwent AN surgery and had normal preoperative facial nerve function. A descriptive analysis was used for the surgical outcomes of each patient. RESULTS: The median age of patients was 51.5 (15.8 SD). Hearing levels pre-operatively were severe to profound in 74.0% of the patients, followed by moderate to severe in 15.1%, mild to moderate in 6.8%, and mild hearing loss in 2.7%. Retrosigmoid (48.1%) was the most common surgical approach used, followed by translabyrinthine (44.2%) and middle cranial fossa (MCF) (7.7%). The translabyrinthine approach is associated with the least incidence of facial nerve paresis postoperatively (21.2%) when compared to the retrosigmoid and middle cranial fossa approaches (40.4%). However, there was no significant association between surgical approaches and facial nerve outcome (p=0.07). CONCLUSION: AN surgery is a safe procedure, regardless of the surgical approach used. There was a significant relationship between tumour size and facial nerve outcome.